RELAXATION DRAWING MODELS - Khushvaqtov Umar Norkobilovich (Galaxy International Interdisciplinary Research Journal, 2021)
Numerical modeling of inverse problem relaxation filtration of a homogeneous liquid in the porous media In thispaper pressure-conductivity and relaxation time for pressure gradient are identified by solving of inverse problem. The regularization method is used for perturbed initial data. Effectiveness of first and second order methods is comparatively analyzed.